Peningkatan Keterampilan Dasar dan Hasil Belajar IPS Melalui Model Pembelajaran Kooperatif Tipe NHT (Numbered Heads Together) - Qoidul Khair (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
Social Studies (IPS) is a program in a lesson that has a scientific field so it is also called a scientific discipline. Social studies also has its own perspective that is integrated from all other subjects and also has a very broad discussion of human behavior that can be studied in detail and studied in depth. Basically social studies has a combination of a number of other subjects, for that social studies is a new field of study, which is then introduced to students. Of all social studies also has basic concepts that must know. For this reason, the purpose of this study is to describe the learning planning, and implementation of learning through cooperative learning model type NHT (Numbered Head Together) that can improve the basic skills of social studies and learning outcomes of classroom students. The method used in this research is Action Research. The results of this study showed an increase in each cycle 1- 3 namely; The value of learning planning becomes very good. The value of teacher performance in learning becomes very good. The achievement of basic social studies skills in students, namely, skillful reached 87%, which means that of the 8 indicators has been achieved as a whole. Increased student learning outcomes, for cycle 1 students who completed reached 20 of the total students, for cycle 2 students who completed reached 26 of the total students and cycle 3 students who completed reached 34.